Perceptual and motor-based responses to hand actions on objects: Evidence from ERPs - Kumar, S; Yoon, E; Humphreys, G (2012)
We carried out a study examining the electrophysiological responses when participants made object decisions to objects and non-objects subject to congruent and incongruent hand-grip actions. Despite the grip responses being irrelevant to the task, event-related potentials were sensitive to the handgrip. There were effects of grip congruency on both P1 and N1 components, over both posterior and motor cortices, with the effects emerging most strongly for familiar objects. In addition, enhanced lateralized readiness potentials were observed for incongruent grips. The results suggest that there are increased perceptual and motor-based responses to objects and object-like stimuli that are grasped correctly, even when the grip is irrelevant to the task. This is consistent with the automatic coding of potential appropriate actions based on visual information from objects in the environment. © Springer-Verlag 2012.